FILM â€œDEATHNOTE THE FIRST NAMEâ€ KARYA TSUGUMI OHBA DALAM PERSPEKTIF SEMIOTIKA CHARLES SANDERS PIERCE - Rudiyanto, Fais; Darmawan, Arif; Jupriono, Jupriono (Universitas 17 Agustus 1945 Surabaya, 2015)
This film begins when Light Yagami finds a book that turned out to belong to a Shinigami (God ofDeath) named Ryuk (Ryuku). In the Death Note Ryuk owned, there are ways to use the Death Notewritten by him alone. Death Note is then used to realize his ideals is to create a clean new world of crime,with himself as a god, by writing the name of the perpetrator into Deathnote book, the offender will dieinstantly in 40 seconds in this study researchers with the theme or topic of fanaticism exist in a moviewith the title